Conditional determinants of FDI in fast emerging economies: an instrumental quantile regression approach - Simplice A. Asongu; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2015)
This paper examines FDI determinants in the BRICS and MINT throughout the conditional distributions of FDI for the period 2001-2011. An instrumental variable quantile regression estimation strategy is employed based on the intuition that, the determinants are contingent on initial or existing FDI levels. The following are some of the findings established. First, FDI benefits of GDP growth are more apparent in nations with higher initial levels of FDI. Second, real GDP output would more positively influence FDI in countries where initial levels of FDI are higher. Hence, the market-seeking purposes increases FDI with a larger magnitude in Higher FDI countries. Third, the impact of trade openness has a Kuznets shape for Gross FDI and increasing tendency for Net FDI. The impact of political stability is only significant for Gross FDI in increasing order.
Keywords: C52; F21; F23; 330; Foreign direct investment; Emerging countries; Quantile regression